Exploring geospatial variation in diabetes-related primary health care service utilisation and potentially preventable hospitalisations in Western Australia - Veenendaal, Bert; Koh, C.; Saleem, Ashty; Varhol, Richard; Xiao, J.; Mai, B.; Liu, Y. (2018)
© Authors 2018. Greater investments and improvements in primary health care (PHC) can provide benefits in reducing the high costs of hospital admissions. Potentially preventable hospitalisations (PPH) are a health system performance indicator used to evaluate access to and effectiveness of community-based health services. The Western Australia Department of Health obtained detailed primary health care data, for the first time at the postcode level scale, and analysed its associations with PPH information for selected conditions. PHC data obtained from the Commonwealth Department of Health for the financial year 2013/14 was Medicare Benefits Schedule (MBS) and Pharmaceutical Benefits Scheme (PBS) records at postcode level. In this paper we explore the sensitivity of various benchmarks of spatial zonings for comparison of diabetes-related primary health care utilisation and potentially preventable hospitalisations and then examine the relationship between them among the various spatial zonings. From the geospatial visualisation and analysis undertaken, conclusions are drawn about the patterns and relationships between diabetes-related primary health care utilisation and potentially preventable hospitalisations. The scale of spatial zonings used for comparison is important as too large or too small areas may mask out the relative geospatial variation of diabetes-related PHC utilisation and PPH evident among postcode areas.